Estrogenic activity and ecological risk of steroids, bisphenol A and phthalates after secondary and tertiary sewage treatment processes. (1st May 2022) - Guo, Wei; Li, Jun; Luo, Mingyue; Mao, Yan; Yu, Xiangyi; Elskens, Marc; Baeyens, Willy; Gao, Yue
Highlights: Steroids and BPA had a higher removal than phthalates in STPs, and mainly by biodegradation. The estrogenic activity of steroids in effluents were higher than that of BPA and phthalates. Tertiary treatment effectively reduced the discharge of steroids and BPA in STPs. E2 contributed more estrogenic activity in effluents based on chemEEQ results. E2 and EE2 in the tertiary effluent posed a moderate risk to the aquatic ecosystem. Abstract: Effluents of sewage treatment plants (STPs) are an important source of estrogenic substances to the receiving water bodies affecting their ecological safety. In this study, steroids, bisphenol A (BPA) and phthalates were assessed in the secondary (SE) and tertiary effluent (TE) of three typical urban STPs in Beijing (China). In addition, the overall estrogenic activity in these effluents was assessed by an in-vitro bioassay (ERE-CALUX). Results showed that the concentrations and activities of estrogenic compounds in TE were lower than those in SE. The residual concentration of 17β-estradiol (E2) was the highest among the detected steroids, accounting for 51.6 ± 5.1% in SE and 57.5 ± 24.8% in TE. The residual level (25.2–41.6 ng/L) of BPA in effluents was significantly higher than that of steroids (0.2–28.8 ng/L). The residual concentration of diethyl phthalate was the highest among the detected phthalates accounting for 47.1 ± 5.1% in SE and 37.6 ± 11.5% in TE. Steroids and BPA had a higher removal rate (83.5% and 96.7%) in secondary and tertiary treatment than phthalates (68.8% and 83.1%). The hydrophobic characteristics of these estrogenic compounds determined the removal mechanism. The removal of steroids, BPA, dimethyl phthalate and diethyl phthalate (Log K ow = 1.61–4.15) mainly occurred through biodegradation in the water phase, while the removal of dibutyl phthalate, butylbenzyl phthalate and di(2-ethylhexyl) phthalate (Log K ow = 4.27–7.50) mainly occurred in the solid phase after adsorption on and sedimentation of the suspended particulate matter. According to ERE-CALUX, the estrogenic activity in the final STP effluents was 3.2–45.6 ng E2 -equivalents/L, which is higher than reported levels in the effluents of European STPs. Calculation of estrogenic equivalents by using substance specific chemical analysis indicated that the dominant contributor was E2 (56.4–88.4%), followed by 17α-ethinylestradiol (EE2) (4.1–34.8%), both also exerting a moderate risk to the aquatic ecosystem. While the upgrade of treatment processes in STPs has efficiently reduced the emission of estrogenic substances, their ecological risk was not yet phased out. Graphical Abstract: Image, graphical abstract .